KARYOTYPE ANALYSIS AND CHROMOSOME NUMBER CONFIRMATION IN TINOSPORA CORDIFOLIA (WILLD.) MIERS. EX HOOK. F. AND THOMAS. A. - RICHA JAIN; BHEEM PRASAD (International Journal of Pharma and Bio Sciences, 2014)
Karyotypic analysis of Tinospora cordifolia (Willd.) was carried out to determine the chromosomal classification by using “Aceto-orcine stain”. The plant is diploid with 2n=22 (18m+2Sm+2St) chromosomes and characterized in eleven pairs of chromosomes. The chromosomes are very short with a mean length 2.64 µm. and the total length of haploid complements was found 29.04 µm. The ideogram of Tinospora cordifolia (Willd.) was prepared for the first time and it was found to be asymmetric. The ideogram confirms the karyotypic formula K (n=11) = 9M+1Sm+1St.